Household arsenic contaminated water treatment employing iron oxide/ bamboo biochar composite: An approach to technology transfer - Alchouron, Jacinta (2021)
Commercialization of novel adsorbents technology for providing safe drinking water must consider scale-up methodological approaches to bridge the gap between laboratory and industrial applications. These imply complex matrix analysis and large-scale experiment designs. Arsenic concentrations up to 200-fold higher (2000 µg/L) than the WHO safe drinking limit (10 µg/L) have been reported in Latin American drinking waters. In this work, biochar was developed from a single, readily available, and taxonomically identified woody bamboo species, Guadua chacoensis. Raw biochar (BC) from slow pyrolysis (700 °C for 1 h) and its analog containing chemically precipitated Fe3O4 nanoparticles (BC-Fe) were produced. BC-Fe performed well in fixed-bed column sorption. Predicted model capacities ranged from 8.2 to 7.5 mg/g and were not affected by pH 5–9 shift. The effect of competing matrix chemicals including sulfate, phosphate, nitrate, chloride, acetate, dichromate, carbonate, fluoride, selenate, and molybdate ions (each at 0.01 mM, 0.1 mM and 1 mM) was evaluated. Fe3O4 enhanced the adsorption of arsenate as well as phosphate, molybdate, dichromate and selenate. With the exception of nitrate, individually competing ions at low concentration (0.01 mM) did not significantly inhibit As(V) sorption onto BC-Fe. The presence of ten different ions in low concentrations (0.01 mM) did not exert much influence and BC-Fe’s preference for arsenate, and removal remained above 90%. The batch and column BC and BC-Fe adsorption capacities and their ability to provide safe drinking water were evaluated using a naturally contaminated tap water (165 ± 5 µg/L As). A 960 mL volume (203.8 Bed Volumes) of As-free drinking water was collected from a 1 g BC-Fe fixed bed. Adsorbent regeneration was attempted with (NH4)2SO4, KOH, or K3PO4 (1 M) strippers. Potassium phosphate performed the best for BC-Fe regeneration. Safe disposal options for the exhausted adsorbents are proposed. Adsorbents and their As-laden analogues (from single and multi-component mixtures) were characterized using high resolution XPS and possible competitive interactions and adsorption pathways and attractive interactions were proposed including electrostatic attractions, hydrogen bonding and weak chemisorption to BC phenolics. Stoichiometric precipitation of metal (Mg, Ca and Fe) oxyanion (phosphate, molybdate, selenate and chromate) insoluble compounds is considered. The use of a packed BC-Fe cartridge to provide As-free drinking water is presented for potential commercial use. BC-Fe is an environmentally friendly and potentially cost-effective adsorbent to provide arsenic-free household water.